The Time Course of the Loss and Recovery of Contracture Ability in Frog Striated Muscle Following Exposure to Ca-Free Solutions - Milligan, J. V. (The Rockefeller University Press, 1965)
Using area under the contracture curve to quantitate contractures, the diffusion coefficient of calcium ions within the frog toe muscle during washout in a calcium-free solution and subsequent recovery after reintroduction of calcium to the bathing solution was calculated to be about 2 x 10-6 cm2/sec. The diffusion coefficient measured during washout was found to be independent of temperature or initial calcium ion concentration. During recovery it was found to decrease if the temperature was lowered. This was likely due to the repolarization occurring after the depolarizing effect of the calcium-free solution. The relation between contracture area and [Ca]o was found to be useful over a wider range than that between maximum tension and [Ca]o. The normalized contracture areas were larger at lower calcium concentrations if the contractures were produced with cold potassium solutions or if NO3 replaced Cl in the bathing solutions. Decreasing the potassium concentration of the contracture solution to 50 mM from 115 mM did not change the relation between [Ca]o and the normalized area. If the K concentration of the bathing solution was increased, the areas were decreased at lower concentrations of Ca.